Cannabinoid Hyperemesis Syndrome. Issue 8 (August 2013) - Sun, Shusen; Zimmermann, Anthony E.
Background: The purpose of this review is to describe cannabinoid hyperemesis syndrome (CHS), which is thought to be induced by long-term cannabis use, and provide clinical pharmacists with information to manage the hyperemetic phase of CHS. Method: Published literature was searched and reviewed using PubMed. Results: CHS is characterized by intractable nausea and vomiting without an obvious organic cause and associated learned compulsive hot water bathing behavior. Patients often seek care in the emergency department (ED) for symptomatic relief. Conclusion: CHS is potentially underrecognized and underdiagnosed in the ED, and it should be considered in the differential diagnosis in long-term cannabis use patients with CHS symptoms to avoid unnecessary extensive diagnostic workup including invasive radiologic imaging. Pharmacists have an important role in CHS recognition, education, and symptom management.